Peran Gender Diversity dalam Memoderasi Pengaruh Pembiayaan Mudharabah dan Musyarakah Bermasalah terhadap Profitabilitas Perbankan Syariah - Mawada, Alifia Aulia; Segaf, Segaf (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the effect of non-performing financing under mudharabah and musyarakah contracts on the profitability of Islamic commercial banks in Indonesia, with gender diversity on the board of directors as a moderating variable. The study population includes all Islamic commercial banks registered with the Financial Services Authority (FSA) for the 2019-2023 period, with a total population of 13 banks, while the sample obtained was 4 Islamic commercial banks. The analysis used in this study was linear regression and moderated regression analysis. The results of this study found that non-performing financing under mudharabah and musyarakah contracts had a significant negative impact on profitability. Furthermore, gender diversity on the board of directors was proven to significantly moderate the relationship between non-performing financing and profitability.